Characteristics of Hepatitis C Virus Infection in HIV-Infected People - Curtis L Cooper; Andrew D Badley; Jonathan B Angel (Canadian Journal of Infectious Diseases)
Knowledge pertaining to hepatitis C virus (HCV)/human immunodeficiency virus (HIV) co-infection is currently incomplete or conflicting. Several points are well studied, however. Plasma HCV RNA levels are higher in matched HIV-infected people than in HIV-seronegative control subjects and are inversely correlated with CD4+ T lymphocyte counts. HCV genotype does not appear to influence this value. Co-infected individuals develop histological and clinical features of HCV liver disease more rapidly than HIV-seronegative patients. Co-infected individuals appear to respond to interferon-alpha therapy equally as well as HIV-seronegative HCV-infected adults, but minimal information exists regarding the efficacy and toxicity of combination HCV therapy (interferon-alpha plus ribavirin) in this population. Adverse consequences of highly active antiretroviral therapy in co-infected patients include hepatic toxicity and, in a minority of patients, an 'immune restoration syndrome'. It is unclear whether long term, highly active antiretroviral therapy positively or negatively influences the natural history of HCV infection.